Financial health, exports, and firm survival: A comparison of British and French firms - Holger Görg; Marina-Eliza Spaliara (Verein für Socialpolitik, 2010)
We examine the differential effects of financial status and exporting activity on the likelihood of survival for firms in the UK and France - two countries with different financial systems. We aim to answer two main questions: What is the direct impact of financial characteristics and different facets of exporting activity on the likelihood of survival? Do the sensitivities of survival incidence to financial variables vary with the exporting status of firms? We find strong evidence that continuous exporters face a higher probability of survival compared to starters, continuous non-exporters and firms exiting the exporting market. Further, important sensitivities of survival prospects to financial indicators are observed for the UK firms which might be explained by the market based economy. Finally, a within and across countries comparison reveals that the survival of exporting groups varies substantially depending on firms' financial status, the financial system and the prolonged participation in the export market.
Keywords: F10; L20; G30; 330; survival; exports; financial health